Debt : definition and coverage : a note. - Baball, Balliram (1991)
Examines factors which underline differences in debt data - differences in purpose, definition, measurement, and projections. These factors manifest themselves in varying degrees in Trinidad and Tobago data reported by official bodies such as the World Bank and the IMF, as well as by agencies in Trinidad and Tobago which report on debt. Reports on an exercise to reconcile the debt statistics contained in the reports of the Central Bank of Trinidad and Tobago and that of the Auditor-General.